Aerosol-generating dental procedures: a reappraisal of analysis methods and infection control measures. (November 2021) - Tan, K.S.; Chew, R.J.J.; Allen, P.F.; Yu, V.S.H.
Summary: Background: Dental aerosol-generating procedures (AGPs) have been associated with risk for transmitting infectious agents. However, existing infection control monitoring studies potentially underestimate the extent of contamination, due to methodological inadequacies. These studies employed settle plate methodology which only captures droplets that land on agar plates, but not those suspended in air. Furthermore, bacterial culture was used to determine the extent of contamination, without accounting for non-bacterial sources of contamination. Aims: This study sought to bridge these gaps by establishing a monitoring protocol involving active aerosol sampling and analysis of two dental AGPs, root canal treatment (RCT) and scaling. Methods: RCT and scaling were performed with standard aerosol mitigation precautions. Aerosols generated throughout each procedure were sampled using the air sampler device, while contamination of operatory fomites and personal protective equipment was sampled using surface swabs, before and post-treatment. The amount of contamination was quantified using bacterial culture and adenosine triphosphate (ATP) assay. Findings: RCT generated insignificant aerosol and splatter, supporting the infection control procedures' effectiveness. Conversely, scaling significantly increased the amount of aerosol and splatter. When comparing bacterial culture and ATP assay, the magnitude of contamination obtained with ATP assay was greater, suggesting that ATP assay may have detected additional contamination of human origin and bacteria that was not recovered by the culture conditions employed. Conclusions: This monitoring protocol is feasible in the dental setting and determines the extent of contamination generated during AGPs. This could be adopted in future studies to overcome the limitations of the existing literature.